Mortality of Shipham residents: 40-year follow-up. - Inskip, H; Beral, V; McDowall, M (1982)
The 1939 populations of Shipham, a village in Somerset with high soil-cadmium levels, and a nearby control village have been followed for 40 years. Death certificates were obtained for those who had died, and the mortality rates were compared with those for England and Wales. Small excesses of hypertensive, cerebrovascular, and genitourinary disease were noted in Shipman but not in the control village. These conditions have been associated wih cadmium toxicity, and so it is possible that cadmium had some influence on the disease pattern in Shipham; but if so, the effect was slight. By contrast, fewer deaths than expected from respiratory disease and cancers were observed in both villages. This gave rise to all-cause mortality rates in Shipham and the control village which were similar and well below the national average.